1993
DOI: 10.1037/0278-7393.19.5.1151
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of diagnostic hypothesis generation: Effects of information, base rates, and experience.

Abstract: Physicians generated diagnostic hypotheses for case histories for which 2 types of diagnoses were plausible, with one having a higher population base rate but less severe clinical consequences than the other. The number of clinical and background symptoms pointing towards the 2 diagnoses was factorially manipulated. The order and frequency with which physicians generated hypotheses varied with the amount of relevant clinical and background information and as a function of population incidence rates, with littl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
127
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(143 citation statements)
references
References 57 publications
11
127
2
Order By: Relevance
“…), as opposed to encountering symbolic descriptions thereof, can strongly influence people's reasoning and judgments (e.g., Gigerenzer et al 1988;Weber et al 1993;Koehler 1996;Hertwig et al 2004). The effect of our physical lottery implementation could be another manifestation of this finding.…”
Section: Discussionmentioning
confidence: 99%
“…), as opposed to encountering symbolic descriptions thereof, can strongly influence people's reasoning and judgments (e.g., Gigerenzer et al 1988;Weber et al 1993;Koehler 1996;Hertwig et al 2004). The effect of our physical lottery implementation could be another manifestation of this finding.…”
Section: Discussionmentioning
confidence: 99%
“…Although much anecdotal evidence suggests that humans are accurate categorizers, and thus should be sensitive to base-rate information, many studies suggest that people underestimate or ignore base-rate information, leading to the claim that often humans show base-rate neglect (see, e.g., Balla, 1982;Balla, Elstein, & Gates, 1983;Casscells, Schoenberg, & Graboys, 1978;Kahneman & Tversky, 1973;Tversky & Kahneman, 1974;however, see Wallsten, 1981;Weber, Bockenholt, Hilton, & Wallace, 1993). These studies used story problems in which information about the category exemplars and base-rates was presented explicitly as percentages or probabilities.…”
Section: Exam-mentioning
confidence: 99%
“…In addition, we found that physicians gave cancer as their main working diagnosis and referred the patient urgently (i.e., within two weeks) much more often with repeated presentations that suggested a worsening of the condition, and more often for the colorectal cancer case, which included "alarm" symptoms, than for the lung cancer case, which included only vague symptoms. and the literature in the field (Dougherty & Hunter, 2003a;Thomas et al, 2008;Weber et al, 1993). It appears to contrast with the literature on base-rate neglect.…”
Section: Discussionmentioning
confidence: 99%
“…First, physicians perceiving a low probability of cancer in patients presenting with vague symptoms may fail to generate the cancer hypothesis or exclude it as an implausible explanation for the patients' symptoms in the hypothesis evaluation phase. Indeed, people tend to first generate the hypotheses with a high a priori probability (Dougherty & Hunter, 2003a;Weber, Böckenholt, Hilton, & Wallace, 1993). Physicians may also fail to diagnose cancer if there is an alternative, more common, explanation for the symptoms in an early stage of the diagnostic process.…”
mentioning
confidence: 99%